IMPLEMENTASI METODE DRILL DALAM PEMBELAJARAN PEMAHAMAN TEKS INFORMASI: STUDI KASUS PADA SISWA SMP MA’ARIF 5 PUCUK KABUPATEN LAMONGAN - Elda Safiro; Warsiman Warsiman (Universitas Negeri Makassar, 2023)
Implementation of the Drill Method in Learning Information Text Comprehension: A Case Study of Students at SMP Ma'arif 5 Pucuk, Lamongan Regency. This study aims to determine the implementation of the use of the drill method as a support for learning reading comprehension of information texts for class VIII students of SMP Ma'arif 5 Pucuk Lamongan. This research is a case study. The research instruments are interviews, observation, and documentation. The results of the study showed that the use of the drill method had an effect on increasing students' grades on informational text reading material. These results can be seen from the students' assessment scores on literacy skills, which show the lowest proportion of students' scores at as much as 7.6%, while the highest proportion of students' scores is 92.3%.